Studi Kasus Pesan Perlawanan Jokowi Dalam Pilpres 2024: Perspektif TIR dan Etika Jawa - Santika, Azzumar Adhitia (Jurnal Common, 2024)
The ‘Party officer’ label which is often communicated by The Indonesian Democratic Party of Struggle (Partai Demokrasi Indonesia Perjuangan/PDIP) to describe Joko Widodo (Jokowi) became a bad political image for him. It is because Jokowi is seen as a man who always obeys the party, and has no power to argue or oppose them. This qualitative research with case study method aims to observe and analyse how the political move from Gibran Rakabuming Raka, the first born of Jokowi, as Prabowo Subianto’s vice president candidate in the 2024 Indonesia Presidential Election (Pemilihan Presiden/Pilpres) could be seen as a symbolic resistance message from Jokowi to PDIP. The result of this research shows that Jokowi uses the denial strategy offered by Theory of Image Restoration (TIR) to deal with the aforementioned bad political image, even though he does not directly deny it, but indirectly through that symbolic resistance message. This also shows that Javanese ethic is an extreme influence to Jokowi on his practice of politics and communications.